Negovanje netrivialnega - Kordeš, Urban (Primerjalna književnost, 2012)
The paper aims to acknowledge the need for renewing the trust in the individuality, complexity and intimacy of direct experience. It delineates limitations of the analytical-reductionist paradigm in the observation of the flow of consciousness, and suggests a balancing the intersubjective reductionist approximation with the intimate reality of the gestalt awareness demonstrated, perhaps better than by anybody else, by literary writers, those careful pursuers of the flow of consciousness.
Keywords: kognitivna znanost; izkustvo; tok zavesti; individualnost; soudeleženost; filozofija; philosophy; psihologija; psychology; literature; književnost